Mechanized Wood Extraction: Impacts on Operators’ Hearing Health - Camargo, Diego Aparecido [UNESP]; Munis, Rafaele Almeida [UNESP]; Miyajima, Ricardo Hideaki [UNESP]; Lima, Roldão Carlos Andrade [UNESP]; Simões, Danilo [UNESP] (MDPI, 2022)
The activity of the mechanized extraction of wood, carried out by means of self-propelled forest machines, consists of moving the wood cut inside the forest stand from the planted forests to the roadside. During displacements, these machines normally travel over forest residues and stumps, which can demand greater motor power from the engine, in addition to the possible increase in occupational noise levels. In this context, we evaluated whether, when operating different self-propelled forest machines in the wood extraction of planted Eucalyptus forests, operators are exposed to different levels of occupational noise, especially to thresholds above those established for prevention purposes. Occupational noise data were collected during the workday, weighing six self-propelled forest machine operators who performed the wood-extraction operation, performed by two forwarders, two self-loading tractors, and two grapple skidders, in three areas with Eucalyptus plantations located in the southeastern region of Brazil. The sound-pressure level was collected using two integrative meters following the strategic measurement criterion recommendation for the whole day in the guidelines of the acoustic determination of occupational noise exposure and analyzed according to the American Conference of Government Industrial Hygienists. Operators of forest machines for the mechanized extraction of wood were exposed to occupational noise levels above the recommended level, which can affect health and well-being; this occupation also required above-average levels of attention during the execution of work activities.
Keywords: ergonomics; Eucalyptus; forest operations; occupational noise; planted forests; wood harvesting